Mixed methods exploration of how people who have experienced psychosis develop a social identity as a ‘person in recovery’ - Deakin, Emilia (2023)
Introduction Personal Recovery involves the development of new meaning and purpose in one’s life as a person grows beyond the effects of mental illness. A key recovery process is redefining and rebuilding a positive sense of identity. The Social Identity Approach provides a theoretical framework for understanding identity changes in recovery. The overall aim of the thesis was to develop a model of social identity change in recovery from psychosis.